Plasma lipidomics of primary biliary cholangitis and its comparison with Sjögren’s syndrome - Li, Haolong; Zhan, Haoting; Cheng, Linlin; Huang, Yuan; Li, Xiaomeng; Yan, Songxin; Liu, Yongmei; Wang, Li; Li, Yongzhe (Frontiers in Immunology, 2023)
Abstract Background: Abnormal lipid metabolism is common in patients with primary biliary cholangitis (PBC). PBC and Sjogren's syndrome (SS) frequently coexist in clinical practice, however, the lipid characteristics of both diseases are unknown. Therefore, we aimed to analyze the plasma lipid profiles of both diseases. Methods: Plasma samples from 60 PBC, 30 SS, and 30 healthy controls (HC) were collected, and untargeted lipidomics was performed using ultra-high-performance liquid chromatography-high-resolution mass spectrometry. Potential lipid biomarkers were screened through an orthogonal projection to latent structures discriminant analysis and further evaluated using receiver operating characteristic (ROC) analysis. Results: A total of 115 lipids were differentially upregulated in PBC compared with HC. Seventeen lipids were positively associated with the disease activity of PBC, and ROC analysis showed that all of these lipids could differentiate between ursodeoxycholic acid (UDCA)-responders and UDCA-non-responders. The top six lipids based on the area under the curve (AUC) values were glycerophosphocholine (PC) (16:0/16:0), PC (18:1/18:1), PC (42:2), PC (16:0/18:1), PC (17:1/14:0), and PC (15:0/18:1). In comparison with SS, 44 lipids were found to be differentially upregulated in PBC. Additionally, eight lipids were found to have a good diagnostic performance of PBC because of the AUC values of more than 0.9 when identified from SS and HC groups, which were lysophosphatidylcholines (LysoPC) (16:1), PC (16:0/16:0), PC (16:0/16:1), PC (16:1/20:4), PC (18:0/20:3), PC (18:1/20:2), PC (20:0/22:5), and PC (20:1/22:5). Conclusion: Our study revealed differentially expressed lipid signatures in PBC compared with HC and SS. PC is the main lipid species associated with disease activity and the UDCA response in patients with PBC.